Endogenously entrained life events of Parthenium beetle, Zygogramma bicolorata Pallister (Coleoptera: Chrysomelidae). Issue 6 (1st November 2016) - Afaq, Uzma; Omkar,
Abstract: Biological rhythm is ubiquitous in all living organisms and is known to govern physiology, behavior, and population of insects. Though these rhythms are generated endogenously, they are entrained by environment. This experiment aims to evaluate the diel rhythms of mating, hatching and oviposition, and the influence of parental mating rhythm on their progeny. Peak of mating and oviposition incidences were recorded during later part of the photophase, which might be ascribed to the foraging rhythm during the day. However, maximum hatching was recorded during the scotophase which appears to be a survival strategy. Mating, oviposition, and hatching rhythms did not change on consecutive days and were thus probably endogenous in nature. It was also observed that the rhythm of parental mating had profound effect on their offspring fitness in terms of development and survival.